Scientific research progress of COVID‐19/SARS‐CoV‐2 in the first five months - Li, Hua; Liu, Zhe; Ge, Junbo (Journal of cellular and molecular medicine, 2020)
A cluster of pneumonia (COVID‐19) cases have been found in Wuhan China in late December, 2019, and subsequently, a novel coronavirus with a positive stranded RNA was identified to be the aetiological virus (severe acute respiratory syndrome coronavirus 2, SARS‐CoV‐2), which has a phylogenetic similarity to severe acute respiratory syndrome coronavirus (SARS‐CoV). SARS‐CoV‐2 transmits mainly through droplets and close contact and the elder or people with chronic diseases are high‐risk population. People affected by SARS‐CoV‐2 can be asymptomatic, which brings about more difficulties to control the transmission. COVID‐19 has become pandemic rapidly after onset, and so far the infected people have been above 2 000 000 and more than 130 000 died worldwide according to COVID‐19 situation dashboard of World Health Organization (https://covid19.who.int). Here, we summarized the current known knowledge regarding epidemiological, pathogenesis, pathology, clinical features, comorbidities and treatment of COVID‐19/ SARS‐CoV‐2 as reference for the prevention and control COVID‐19.